Stopping Traffic? A Comparative Study of Responses to the Trafficking in Women for Prostitution - Munro, Vanessa E. (The British journal of criminology, 2006)
Set against the backdrop of counter-trafficking initiatives at international level, this article draws on the findings of a comparative study that investigated (through semi-structured interviews with officials and interest groups) the merits and demerits of domestic level responses in the United Kingdom, Australia, Holland, Sweden and Italy. In a context in which trafficking in women for sexual purposes can be understood through the lens of numerous frameworks (human rights, criminality, prostitution policy, immigration, social exclusion, etc.), this article examines the extent to which these different agendas have influenced the construction and operation of the respective domestic regimes. More specifically, it illustrates the extent to which the ambiguities inherent in the United Nation's most recent Anti-Trafficking Protocol permit scope for the incorporation and/or perpetuation of discretion at domestic level. Highlighting the underlying tensions between competing immigration, human rights, policing and social services imperatives, the differential resolution of which leads to the divergence in domestic response, this article situates this complex engagement in the broader context of debates about globalization, exploitation and prostitution